Coordinating VATs Between EU Member States - Bernd Genser (Center for Economic Studies and ifo Institute (CESifo), 2002)
The paper surveys the characteristics of the common European VAT system, proposed by the EU-Commission to overcome the weaknesses of the transitional European VAT system, which was enacted in 1993 and is still in force. We argue that a harmonized VAT rate will generate substantial costs for EU member states to meet national budget requirements and that the revenue sharing mechanisms will generate adverse incentives to national efforts in VAT collection and control. A comparison of the Commission proposal with four alternative VAT regimes favours a modified VIVAT system as an attractive compromise.
Keywords: 330; value-added taxation; tax coordination.